2017
DOI: 10.18632/oncotarget.23635
|View full text |Cite
|
Sign up to set email alerts
|

High RAC3 expression levels are required for induction and maintaining of cancer cell stemness

Abstract: RAC3 is a transcription coactivator, usually overexpressed in several tumors and required to maintain the pluripotency in normal stem cells.In this work we studied the association between RAC3 overexpression on cancer cell stemness and the capacity of this protein to induce cancer stem properties in non tumoral cells.We performed in vitro and in vivo experiments using two strategies: by overexpressing RAC3 in the non tumoral cell line HEK293 and by silencing RAC3 in the human colorectal epithelial cell line HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
(77 reference statements)
2
5
0
Order By: Relevance
“…As previously demonstrated (Panelo et al, 2018[ 25 ]), although HEK293 cells express moderated levels of the mesenchymal marker Vimentin, they were significantly increased when RAC3 was overexpressed, while E-Cadherin was significantly inhibited (Figure 1A and B (Fig. 1) ).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…As previously demonstrated (Panelo et al, 2018[ 25 ]), although HEK293 cells express moderated levels of the mesenchymal marker Vimentin, they were significantly increased when RAC3 was overexpressed, while E-Cadherin was significantly inhibited (Figure 1A and B (Fig. 1) ).…”
Section: Resultssupporting
confidence: 82%
“…We have previously found that RAC3 has a transforming role in HEK293 cells when is overexpressed by stable transfection, acquiring not only the ability to grow in an anchorage-independent manner (Rubio et al, 2012[ 30 ]) but also to initiate tumors when are inoculated to mice (Panelo et al, 2018[ 25 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations